Clinical evaluation of super-responders vs. non-responders to CGRP(-receptor) monoclonal antibodies: a real-world experience - Bianca Raffaelli; Mira Fitzek; Lucas H. Overeem; Elisabeth Storch; Maria Terhart; Uwe Reuter (The Journal of Headache and Pain, 2023)
Abstract Background Clinical trials and real-world studies revealed a spectrum of response to CGRP(-receptor) monoclonal antibodies (mAbs) in migraine prophylaxis, ranging from no effect at all to total migraine freedom. In this study, we aimed to compare clinical characteristics between super-responders (SR) and non-responders (NR) to CGRP(-receptor) mAbs. Methods We performed a retrospective cohort study at the Headache Center, Charité – Universitätsmedizin Berlin. The definition of super-response was a ≥ 75% reduction in monthly headache days (MHD) in the third month after treatment initiation compared to the month prior to treatment begin (baseline). Non-response was defined as ≤ 25% reduction in MHD after three months of treatment with a CGRP-receptor mAb and subsequent three months of treatment with CGRP mAb, or vice versa. We collected demographic data, migraine disease characteristics, migraine symptoms during the attacks in both study groups (SR/NR) as well as the general medical history. SR and NR were compared using Chi-square test for categorical variables, and t-test for continuous variables. Results Between November 2018 and June 2022, n = 260 patients with migraine received preventive treatment with CGRP(-receptor) mAbs and provided complete headache documentation for the baseline phase and the third treatment month. Among those, we identified n = 29 SR (11%) and n = 26 NR (10%). SR reported more often especially vomiting (SR n = 12/25, 48% vs. NR n = 4/22, 18%; p = 0.031) and typical migraine characteristics such as unilateral localization, pulsating character, photophobia and nausea. A subjective good response to triptans was significantly higher in SR (n = 26/29, 90%) than in NR (n = 15/25, 60%, p = 0.010). NR suffered more frequently from chronic migraine (NR n = 24/26, 92% vs. SR n = 15/29, 52%; p = 0.001), medication overuse headache (NR n = 14/24, 58% versus SR n = 8/29, 28%; p = 0.024), and concomitant depression (NR n = 17/26, 65% vs. SR n = 8/29, 28%; p = 0.005). Conclusion Several clinical parameters differ between SR and NR to prophylactic CGRP(-R) mAbs. A thorough clinical evaluation prior to treatment initiation might help to achieve a more personalized management in patients with migraine.